Pulmonary Hypertension and Interstitial Lung Disease - Baughman, Robert P.; Carbone, Roberto G.; Nathan, Steven D. (Springer International Publishing : Imprint: Springer, 2017)
The first edition of this book, published in 2009, was the only book of its kind dedicated exclusively to the diagnosis and management of pulmonary arterial hypertension (PAH) in patients with interstitial lung disease (ILD). Over the past few years, new diagnostic tests and treatments of pulmonary arterial hypertension have been developed and tested. Diagnostic testing has led to more frequent and specific diagnosis in PAH patients, leading to the more widespread use of effective treatment and improved quality of life and reduction of mortality for PAH patients. Pulmonary Hypertension and Interstitial Lung Disease: A Clinical Guide, Second Edition provides an updated and expanded state-of-the-art overview of the problems seen by physicians in the clinical management of ILDs. The first section of the book discusses general features and includes an overview of clinical features, diagnosis and pathology of ILD. The second part discusses specific disorders such as idiopathic pulmonary fibrosis, sarcoidosis, and hypersensitivity pneumonia. Pulmonary Hypertension and Interstitial Lung Disease, Second Edition is an invaluable resource for all physicians whose practice involves the care and treatment of patients with interstitial lung disease.